Seismic behavior and design of cruciform bolted module-to-module connection with various reinforcing details. (December 2018) - Deng, En-Feng; Zong, Liang; Ding, Yang; Luo, Yun-Biao
Abstract: Modular steel constructions (MSC) permits rapid and economical construction and have been increasingly used for high-rise buildings with repetitive units. A new bolted connection with welded cover plate, which can better satisfy the architectural function design, was proposed in this paper. Tests on four full-scale cruciform connections made of hollow structural section (HSS) members with various configurations were conducted under combined axial compression and increasing cyclic rotations to failure. The results showed that the moment resistance capacity of the unreinforced connections was limited due to the brittle weld fracture at the end of the beam while that of the reinforced connections was enhanced considerably, either by external cover plate or triangular-shaped stiffeners, which can guarantee the desired seismic resistance. The seismic performance, including the initial rotational stiffness, moment resistance, ductility and energy dissipation were carefully evaluated. EC3 Part 1–8 was adopted to evaluate the stiffness characteristic of the proposed connection, indicating that the proposed connection can be classified as "semi-rigid" connection. Furthermore, mechanical model was developed and design recommendations were given based on the test results, which will provide useful references for the application of the proposed connection and MSC in seismic region. Highlights: An innovative connection for modular steel construction was proposed. The proposed connection works well with building function. Four cruciform full-scale specimens were tested under cyclic load. Load-transferring mechanism and seismic performance were investigated. Design considerations were recommended for the proposed connection.